1987
DOI: 10.3765/bls.v13i0.1828
|View full text |Cite
|
Sign up to set email alerts
|

Tone and Melody in Cantonese

Abstract: Proceedings of the Thirteenth Annual Meeting of the Berkeley Linguistics Society (1987), pp. 26-37

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
2
15
0
1
Order By: Relevance
“…35 For discussions of parallels and contrasts between music and speech see, for example, Fónagy (1981), Fujisaki (1983), Lerdahl and Jackendoff (1983), Chan (1987), Carlsen et al (1989), Scotto di Carlo and Autesserre (1992), Patel (1998), Patel et al (1998), Ross and Lehiste (2001), Arnold and Jusczyk (2002), Lehiste (2004), Martin (2004), and Dilley (2005 As we can see, the pitch is 440 Hz from the beginning of the sounding of this note to its end (which is from 1.09 s to 2.55 s on the time axis). In contrast to this, the pitches of words in speech are not kept constant, i.e., when a word is uttered, the pitch curve in the duration of a syllable is not a straight line (the only exception being the chanted call where syllables have constant pitches).…”
Section: The Melody Of Wordsmentioning
confidence: 99%
“…35 For discussions of parallels and contrasts between music and speech see, for example, Fónagy (1981), Fujisaki (1983), Lerdahl and Jackendoff (1983), Chan (1987), Carlsen et al (1989), Scotto di Carlo and Autesserre (1992), Patel (1998), Patel et al (1998), Ross and Lehiste (2001), Arnold and Jusczyk (2002), Lehiste (2004), Martin (2004), and Dilley (2005 As we can see, the pitch is 440 Hz from the beginning of the sounding of this note to its end (which is from 1.09 s to 2.55 s on the time axis). In contrast to this, the pitches of words in speech are not kept constant, i.e., when a word is uttered, the pitch curve in the duration of a syllable is not a straight line (the only exception being the chanted call where syllables have constant pitches).…”
Section: The Melody Of Wordsmentioning
confidence: 99%
“…However, there are some extracted onset times which are in fact not vocal. So, 4 Due to limited space, the experimental result is put in the appendix available at http://www.cse.cuhk.edu. hk/∼khwong/demo/lyricsalign/demo.htm.…”
Section: Non-vocal Pruningmentioning
confidence: 99%
“…Figure 9 shows the idea of the relative pitch matching of a Cantonese song. In our system, we follow the categorization of 6 tones of Cantonese into three groups in [4]: high, mid and low pitches. Each group is called lyrics pitch LP.…”
Section: Relative Pitch Featurementioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have observed that, in Cantonese lyrics writing for pop music, the low-rising 23 and mid-level 33 are interchangeable, whereas the high-rising 25 and the high-level 55 are interchangeable (Chan 1987;Ho 2006). The tones are interchangeable in the sense that, for example, if the tone 23 is compatible with a particular musical note, then 33 is also compatible; see the references cited for more musical details.…”
Section: 3mentioning
confidence: 99%